A look at the contributions of indigenous and African peoples to Brazilian food culture: a proposal for science teaching (Olhar de Professor, 2022)
This article brings the results of an action research, whose objective was to analyze how the contents on nutrition can be allied to the ethnic-racial perspective, based on the law 11.645 (BRASIL, 2008), which establishes the mandatory nature of the theme and Indigenous History and Culture" in the school curriculum. Thus, to discuss the importance of food cultural diversity in science classes in the final years of elementary school. For this, interventions were carried out in an 8th grade class of an Countryside school, located in the municipality of “Nova Esperança -Paraná”. From the activities, which aimed at the multicultural formation of students, leading them to reflect on the need for respect and knowledge of the culture of African and indigenous peoples, we can observe that interactions with our culture are relevant to the social formation of subjects, a time to integrate the school community with the different contexts. Thus, activities with this focus are important in bringing culture and science closer together.